Remote results of modern surgical approaches in the treatment of esophageal cancer (Texas Journal of Medical Science, 2025)
Esophageal cancer remains one of the most aggressive forms of gastrointestinal malignancy, characterized by a high mortality rate and poor prognosis. Surgery, often combined with chemoradiation, remains the primary definitive treatment option. In recent years, considerable attention has been paid to the analysis of long-term outcomes, including overall and disease-free survival, quality of life, and the incidence of complications and tumor recurrence. This paper presents summarized clinical observational da ta characterizing the long-term effectiveness of surgical treatment. Key factors influencing survival are identified, including tumor morphology, degree of invasion, surgical radicality, resection margin status, and comorbidities. A comparative analysis of the outcomes of open and minimally invasive procedures is also conducted. The data obtained confirm the need for a comprehensive approach, multidisciplinary monitoring, and optimized postoperative patient care to improve five-year survival.